Thermal insulator coating from recycling of municipal solid waste incinerator bottom ash - Feryal Rezaee Mood, 1972-; Mohd. Hamdan Ahmad, supervisor; Fakulti Alam Bina (2014)
Thesis (Ph.D (Senibina)) - Universiti Teknologi Malaysia, 2014